Ruralization vs. Urbanization Sprawl as Guiding Regional Planning: Development Scenario for Rivers Watershed in the Southern Syrian Coastal Region. (May 2018) - Rahmoun, T; Zhao, W; Hammad, M; Hassan, M
Abstract: This study aimed at opening discussions concerning new ideas of suggesting sustainable scenario based on the principle of an integrated spatial development ring between urban-rural areas along and between AL-Abrash and AL-Hseen rivers watershed, as an application of the bottom-up planning model, seeking to achieve ruralization in parallel with urbanization. This paper adopted data collections and analysis through using a step-by-step approach. Firstly, investigated the land-cover change (LCC) during 30-years. Therefore, using multi-temporal satellite data from different dates for the same study area to create thematic land cover maps which can be used for land cover change detection. Three Landsat satellite images from1987, 2002 and 2017 were classified separately using the supervised classification method in ArcGIS, to provide an economical way to quantify, map and analyse changes over time in land cover. Then, SWOT analysis for the possibilities and determinants within the two-way flow of the current and futuristic economic activity, besides discussion the opportunities of the land-use (LU) taking into account slop map to achieve conservation priority for natural resources. Finally, evaluate results and establishing a sustainable spatial scenario approachable to upgrade into scaling up/out to covering the coastal region watersheds, can support regional planning and decision-making in the future.